2021
DOI: 10.1016/j.conctc.2021.100755
|View full text |Cite
|
Sign up to set email alerts
|

A randomized and comparative study to assess safety and efficacy of supplemental treatment of a herbal formulation - Aayudh Advance comprising essential oils in patients with corona virus 2019 (COVID-19)

Abstract: Objective The purpose of this study was to examine the effect of herbal formulation - Aayudh Advance on viral load as well as recovery duration in mild symptomatic patients diagnosed with Corona Virus Disease 2019 (COVID-19). It also aimed to study the effect of Herbal formulation – Aayudh Advance in terms of clinical improvement of various sign and symptoms in mild symptomatic COVID-19 patients. Method Once the patient suffice the requirement of inclusion, exclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Out of 32 studies, 4 studies have not mentioned gender characteristics of the sample. 16 , 17 , 18 , 19 Overall, there were 56.96% male and 43.03% female patients. The basic characteristics of the RCTs included in the review are mentioned in Table 1 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Out of 32 studies, 4 studies have not mentioned gender characteristics of the sample. 16 , 17 , 18 , 19 Overall, there were 56.96% male and 43.03% female patients. The basic characteristics of the RCTs included in the review are mentioned in Table 1 .…”
Section: Resultsmentioning
confidence: 94%
“…Six studies 17 , 18 , 26 , 30 , 33 , 34 have reported the effect of herbal intervention on improvement in number of days for hospital stay. The overall combined effect rate is represented by MD + CI (n = 388, MD -1.82; 95% CI -3.84, 0.21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As most of the proposed herbal treatments need to be evaluated in vivo, some recent publications were also reviewed. A randomized and comparative study to assess the safety and efficacy of supplemental treatment of a herbal formulation enriched with essential oils named “Aayudh Advance” on viral load as well as recovery duration in mild symptomatic patients diagnosed with COVID-19 was carried out by Dutt et al (2021) . They used 'Covariate Adaptive Randomization' treatment technique for 14 days and reviewed the clinical signs and symptoms and compared with traditional biochemical testing.…”
Section: Existing Trials Prospects Repurposing Possibilities and Chal...mentioning
confidence: 99%
“…The Corona Virus first appeared in December 2019 in Wuhan City, Hubei Province, China (Fang-Guo et al, 2020). The Corona Virus can infect and cause respiratory diseases (Dutt , Jayesh;Ganatra , Bhavdeep;Suthar , Nilay ;Malek , Mohammedebrahim ;Shuklad , Bhakti;Shukla , Krupali;Shukla , Karna ;Pandit , Shreya;Rachchh , Manish;Gokanif, 2021). It is not yet clear how this virus is transmitted.…”
Section: Introductionmentioning
confidence: 99%